Pemanfaatan Teknologi Informasi dan Komunikasi dalam Penerapan Konsep Smart Tourism di Kabupaten Pangandaran - Rifki Rahmanda Putra; Ute Lies Siti Khadijah; Cecep Ucu Rakhman (Magister Tourism Study, Faculty of Tourism, Udayana University, 2020)
Information and communication technology have changed globally specifically in the industrial era 4.0. Pangandaran Regency which focuses its economy through the tourism industry and aspires its region as a world-class tourist destination needs to accelerate its tourism development through the development of information and communication technology with the concept of smart tourism, to initiate an increase with the need to visit tourists. So this study discusses the use of potential and develops the concept of intelligent tourism in The Pangandaran Regency by utilizing information and communication technology to accelerate to become a world-class tourist destination. The method used in this research is qualitative research with case studies, with interactive model analysis techniques. The results showed that the potential of smart tourism in The Pangandaran Regency is a technology-based infrastructure that supports websites, social media, recommendation systems and also the number of millennial tourists. While the development of the concept of smart tourism is divided into the factors of demand and supply with collaboration while the manager of the destination, and the development of intelligent technology by considering Big Data and supporting factors for efficient digital marketing. Keywords: smart tourism, Pangandaran Regency, information and communication technology